Mental health in children: a view on social attribute - Sundaram, Ramkumar; A. M., Shagirunisha Rizvana; T., Aishwarya; V., Anbarasan; S. M., Ganesh Babu (International Journal Of Community Medicine And Public Health, 2021)
Child and adolescence are crucial periods to promote emotional well-being as the greater part of psychological issues start at these stages, and a large number of these continue for the rest of the life. Right now, this has become a need as overall information shows an increase in the pervasiveness of emotional well-being issues in childhood and adolescence and the level of those coming to almost 20%. Factors affecting mental health are familial factors, social and environment, media, physical activity, chronic illness in child, abuse, and bereavement. These factors affect the child’s mental health from their early stages of life. Thus remembering the effect from these factors the child’s mental health to be improved. Large numbers of the psychological wellness programs carried out in schools advance the improvement of social abilities, socio-enthusiastic capabilities, and learning results while simultaneously diminishing problematic behaviour.